8^3-2.(x-1)=4096
512.2.(x-1)=4096
2.(x-1)=4096:512
2.(x-1)=8
x-1=8:2
x-1=4
x =4+1
x =5
\(\left(325-317\right)^3-2\left(x-1\right)=2^{18}:8^2.\)
\(\left(325-317\right)^3-2\left(x-1\right)=2^{18}:\left(2^3\right)^2\)
\(\left(325-317\right)^3-2\left(x-1\right)=2^{18}:2^6\)
\(\left(325-317\right)^3-2\left(x-1\right)=2^{12}\)
\(8^3-2\left(x-1\right)=2^{12}\)
\(\left(2^3\right)^3-2\left(x-1\right)=2^{12}\)
\(2^9-2\left(x-1\right)=2^{12}\)
\(2\left(x-1\right)=2^9-2^{12}\)
\(2\left(x-1\right)=-3584\)
\(\left(x-1\right)=-2584:2\)
\(x-1=-1792\)
\(x=-1792+1\)
\(x=-1791\)
\(\left(325-317\right)^3-2\left(x-1\right)=2^{18}:8^2\)
\(\left(325-317\right)^3-2\left(x-1\right)=\frac{2^{18}}{8^2}\)
\(512-2\left(x-1\right)=4906\)
\(512-2\left(x-1\right)-512=4096-512\)
\(-2\left(x-1\right)=3584\)
\(\frac{-2\left(x-1\right)}{-2}=3584\)
\(\frac{-2\left(x-1\right)}{-2}=3584:\left(-2\right)\)
\(x-1=-1792\)
\(x-1+1=\left(-1792\right)+1\)
\(x=-1791\)
\(\Rightarrow x=-1791\)